Mapping Adverse Outcome Pathways for Kidney Injury as a Basis for the Development of Mechanism-Based Animal-Sparing Approaches to Assessment of Nephrotoxicity - Mally, Angela; Jarzina, Sebastian (Frontiers in Toxicology, 2022)
In line with recent OECD activities on the use of AOPs in developing Integrated Approaches to Testing and Assessment (IATAs), it is expected that systematic mapping of AOPs leading to systemic toxicity may provide a mechanistic framework for the development and implementation of mechanism-based in vitro endpoints. These may form part of an integrated testing strategy to reduce the need for repeated dose toxicity studies. Focusing on kidney and in particular the proximal tubule epithelium as a key target site of chemical-induced injury, the overall aim of this work is to contribute to building a network of AOPs leading to nephrotoxicity. Current mechanistic understanding of kidney injury initiated by (1) inhibition of mitochondrial DNA polymerase  (mtDNA Pol), (2) receptor mediated endocytosis and lysosomal overload, and (3) covalent protein binding, which all present fairly well established, common mechanisms by which certain chemicals or drugs may cause nephrotoxicity, is presented and systematically captured in a formal description of AOPs in line with the OECD AOP development programme and in accordance with the harmonized terminology provided by the Collaborative Adverse Outcome Pathway Wiki. The relative level of confidence in the established AOPs is assessed based on evolved Bradford-Hill weight of evidence considerations of biological plausibility, essentiality and empirical support (temporal and dose-response concordance).